Lithium ion cylindrical battery and preparation method thereof

By using an inorganic-organic hybrid coating in the separator of lithium-ion cylindrical batteries, combined with lithium supplementation composite materials and phosphate flame retardants, the problems of volume expansion, low conductivity and insufficient separator heat resistance of high silicone system batteries are solved, and the battery's high cycle stability and safety performance are achieved.

CN119674271APending Publication Date: 2025-03-21JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411797266.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Due to the volume expansion and low conductivity of silicon-based materials, high silicon system cylindrical lithium-ion batteries have low efficiency, high capacity attenuation rate, poor cycle stability, and insufficient heat resistance, electrolyte wetting and mechanical strength of traditional polyolefin separators, which affect the safety and performance of the battery.

Method used

The inorganic-organic hybrid coating is used as the separator. The slurry in the coating includes inorganic substances, organic polymers, lithium supplementation agent composite materials and phosphate flame retardants. The lithium supplementation agent-carbon nanotube composite materials are prepared by spray drying to enhance the conductivity and conduction ability of the separator, and the cycling stability and safety performance of the battery are improved through the sustained release effect of phosphate flame retardants.

Benefits of technology

By adding lithium supplement composite materials and phosphate flame retardants to the separator, the battery can be continuously supplemented with lithium during the charging and discharging cycle, the battery's circulation capacity retention rate and electrolyte wetting properties are improved, the risk of diaphragm fatigue damage is reduced, and the battery's safety performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674271A_ABST
    Figure CN119674271A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a cylindrical lithium ion battery and a preparation method thereof.The cylindrical lithium ion battery comprises a shell, a roll core and electrolyte, the roll core and the electrolyte are located in the shell, the roll core is formed by winding a positive plate, a diaphragm and a negative plate together, the diaphragm comprises a base film and an inorganic-organic mixed coating arranged on the base film in a coating mode, slurry of the inorganic-organic mixed coating comprises at least one or two of an inorganic substance, an organic polymer, a lithium supplement composite material and a phosphate flame retardant; the lithium supplement agent is added into the inorganic-organic mixed coating of the diaphragm, so that the composite material can be decomposed in the charge-discharge cycle process of the battery, and continuous lithium supplement is realized. And the flame retardant cannot be released in the electrolyte under the constraint of the organic polymer, so that the influence of direct dissolution of the flame retardant in the electrolyte on viscosity and ionic conductivity is avoided, and the cycle performance of the battery is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion cylindrical battery and a preparation method thereof. Background Art

[0002] As a widely used energy storage device in recent years, lithium-ion batteries can provide energy support for many products such as electric vehicles, consumer electronics, and power tools, showing a huge market prospect. At present, the market demand for large-capacity, high-energy-density lithium-ion batteries is increasing rapidly, and the safety performance of lithium-ion batteries is also facing a huge test.

[0003] Cylindrical batteries are favored by the market due to their high energy density, excellent rate performance, mature production process and good consistency. Among them, high-silicon system cylindrical batteries can not only meet the current market's urgent demand for high energy density, but also have a relatively low cost advantage. However, silicon-based materials have the disadvantages of severe volume expansion and low electrical conductivity, resulting in low coulombic efficiency in the first cycle of the battery, high capacity decay rate, poor cycle stability and other problems, which greatly limits the widespread application of high-silicon system cylindrical batteries. The stress generated by the volume expansion of silicon-based negative electrode materials during the charging and discharging process may cause fatigue damage to the diaphragm, and then cause safety problems such as short circuit, pole piece fracture and structural collapse. However, traditional polyolefin diaphragms have poor heat resistance, insufficient electrolyte wettability, poor mechanical strength and other problems. Therefore, they need to be modified to meet the requirements of high-silicon system cylindrical batteries for safety, charging and discharging performance and cycle life.

[0004] Currently, diaphragm companies mainly adopt the method of coating and modifying polyolefin diaphragms to improve the mechanical strength, thermal stability and electrolyte wettability of diaphragms. However, the existing single-coating diaphragms often cannot take into account both the electrochemical performance and safety performance of the battery. Therefore, further developing a hybrid coating diaphragm with comprehensive performance for application in cylindrical batteries has become the key to meeting the market's dual requirements for high energy density and safety performance. Summary of the invention

[0005] The present invention aims to provide a lithium ion cylindrical battery and a preparation method thereof.

[0006] The technical solution of the present invention is:

[0007] A lithium-ion cylindrical battery comprises a shell, a winding core placed in the shell and an electrolyte, wherein the winding core is formed by winding a positive electrode sheet, a separator and a negative electrode sheet together, the separator comprises a base film and an inorganic-organic hybrid coating coated on the base film, and the slurry of the inorganic-organic hybrid coating comprises an inorganic substance, an organic polymer, and one or both of a lithium supplement agent and a phosphate flame retardant.

[0008] In an optional embodiment, the mass ratio of inorganic matter, organic polymer, lithium supplement composite material and phosphate flame retardant in the slurry of the inorganic-organic hybrid coating is 1: (0.05-0.20): (0.1-0.4): (0.01-0.08); and the mass proportion of lithium element in the inorganic-organic hybrid coating is a, satisfying 0.1%≤a≤3%; the mass proportion of phosphate flame retardant in the inorganic-organic hybrid coating is b, satisfying 1%≤b≤5%.

[0009] In an optional embodiment, the organic polymer includes a combination of at least one or more of aramid, polymethyl methacrylate and polyvinylidene fluoride; the inorganic substance includes a combination of at least one or more of boehmite, magnesium hydroxide, aluminum oxide, silicon oxide and zirconium oxide.

[0010] In an optional embodiment, the lithium supplement used in the lithium supplement composite material includes lithium carbonate, lithium oxalate, Li 2 NiO 2 , lithium squarate and Li 2 A combination of at least one or more of S. The lithium supplement agent and carbon nanotubes are mixed and then spray-dried to prepare a lithium supplement agent-carbon nanotube composite material with a small particle size, i.e., a lithium supplement agent composite material, to enhance its ion conductivity and electronic conductivity, thereby reducing the decomposition potential of the lithium supplement agent. The carbon nanotubes account for 1% to 5% of the mass of the lithium supplement agent composite material.

[0011] In an optional embodiment, the phosphate flame retardant includes a combination of at least one or more of triethyl phosphate, trimethyl phosphate, triisopropyl phosphate, tri-n-butyl phosphate, tri(2-chloropropyl) phosphate, tri(2-chloroethyl) phosphate, and triphenyl phosphate.

[0012] In an optional embodiment, the positive electrode sheet includes a positive electrode collector and a positive electrode coating coated on at least one surface of the positive electrode collector, and the positive electrode active material in the positive electrode coating includes a combination of at least one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium iron phosphate and lithium manganese iron phosphate; the negative electrode sheet includes a negative electrode collector and a negative electrode coating coated on at least one surface of the negative electrode collector, and the negative electrode active material in the negative electrode coating includes a combination of at least two or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material and silicon-based alloy, and the silicon mass fraction c in the negative electrode sheet coating is 2%-30%.

[0013] In an optional embodiment, the silicon mass percentage in the negative electrode coating is c, the tensile strength of the diaphragm is T MPa, the pore tortuosity of the diaphragm is τ, and at least one of the following relationships is satisfied: T≥120c+100; 20c+1.6≥τ≥10c+1.6.

[0014] In an optional embodiment, the mass percentage of silicon in the negative electrode coating is c, and the mass percentage of lithium in the diaphragm coating is a, satisfying the following relationship: 0.4≥a / c≥0.05.

[0015] In an optional embodiment, the base film includes any one of a polyethylene film, a polypropylene film, and a polyethylene / polypropylene composite film; the polyethylene / polypropylene composite film includes at least one layer of polyethylene film and at least one layer of polypropylene film; and the thickness of the base film is 7 μm-16 μm.

[0016] In an optional embodiment, the lithium-ion cylindrical battery has a diameter of 20-50 mm and a height of 50-150 mm.

[0017] Another technical solution of the present invention is:

[0018] A method for preparing a lithium-ion cylindrical battery as described above comprises the following steps: step S1, dispersing an inorganic substance, an organic polymer, and one or both of two materials, a lithium supplement composite material and a phosphate flame retardant, in an organic solvent to form a mixed dispersion, adjusting the solid content, and obtaining a coating slurry; step S2, coating the slurry on at least one side of a base film, and forming an inorganic-organic mixed coating with a thickness of 2-5 μm after drying to obtain a composite diaphragm; step S3, winding the positive electrode sheet, the diaphragm, and the negative electrode sheet together to form a winding core, wherein an empty foil area is provided at the edges of the positive and negative electrodes, one end of the cylindrical winding core is connected to the negative electrode busbar by welding, the negative electrode busbar is connected to the outer shell by welding, the other end of the cylindrical winding core is connected to the positive electrode busbar by welding, an insulating sheet is placed on the positive electrode busbar, the positive electrode busbar is connected to the cap by welding, and then an electrolyte is injected, and finally a groove is rolled and sealed to obtain a lithium-ion cylindrical battery.

[0019] The present invention provides a lithium ion cylindrical battery and a preparation method thereof, which has the following beneficial effects:

[0020] 1. Electrochemical performance: By adding lithium replenisher composite materials to the inorganic-organic hybrid coating of the diaphragm, it can be decomposed during the battery charge and discharge cycle to achieve continuous lithium replenishment. Due to the temperature rise effect during the battery charge and discharge process, part of the phosphate flame retardant in the coating can be slowly released into the electrolyte, which can not only act as a hydrogen bond receptor to limit the activity of free water, but also as a film-forming additive to manipulate Li + Solvation structure can be used to stabilize phosphorus-rich and fluorine-rich SEI, reduce the effect of flame retardant added directly to the electrolyte on viscosity and ionic conductivity, and improve battery cycle capacity retention rate. At the same time, the organic-inorganic hybrid coating can improve the electrolyte wettability of the diaphragm, increase the liquid absorption rate and ionic conductivity of the diaphragm, inhibit the growth of lithium dendrites, and improve the battery cycle stability.

[0021] 2. Safety performance: The inorganic ceramic particles added to the diaphragm coating can improve the thermal stability of the diaphragm, and the organic high molecular polymer added to the diaphragm coating has good adhesion. Mixing with inorganic materials can enhance the mechanical properties of the diaphragm, effectively alleviate the silicon volume expansion stress, and reduce the risk of fatigue damage to the diaphragm; the decomposition products of the flame retardant added to the diaphragm coating at high temperatures can isolate oxygen and heat, inhibit the combustion process, and reduce the risk of thermal runaway. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the assembly of a lithium-ion cylindrical battery provided in an embodiment of the present disclosure;

[0023] Figure 2 A schematic diagram of the structure of an inorganic-organic hybrid coating provided in an embodiment of the present disclosure;

[0024] Figure 3 A schematic diagram of the structure of the positive electrode sheet provided in an embodiment of the present disclosure;

[0025] Figure 4 A schematic diagram of the structure of the negative electrode sheet provided in an embodiment of the present disclosure;

[0026] Figure 5 This is a 1C discharge capacity cycle comparison chart of the lithium-ion cylindrical battery provided in the embodiment of the present disclosure.

[0027] In the figure:

[0028] 1. Shell; 2. Positive terminal; 3. Negative terminal; 4. Positive electrode column; 5. Base film; 6. Inorganic-organic hybrid coating; 7. Pores; 8. Positive uncoated area; 9. Ceramic coating area; 10. Positive electrode coating pattern; 11. Negative electrode coating area; 12. Negative electrode uncoated area. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.

[0031] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0032] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.

[0033] Traditional organic-inorganic hybrid coating diaphragms do not have targeted diaphragm pore tortuosity, porosity, mechanical strength, thermal stability and other performance designs for high-silicon negative electrode system cylindrical batteries, and cannot meet the performance requirements of high-silicon cylindrical batteries for diaphragms. In addition, the addition of flame retardants to the electrolyte will have a significant impact on the viscosity and conductivity of the electrolyte, thereby affecting the cycle stability of the battery.

[0034] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present invention.

[0035] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0036] See also Figure 1 ,like Figure 1 As shown, an embodiment of the present disclosure provides a lithium-ion cylindrical battery, comprising a shell, a winding core loaded into the shell and an electrolyte, wherein the winding core is formed by winding a positive electrode sheet, a separator and a negative electrode sheet together, the separator comprises a base film and an inorganic-organic hybrid coating coated on the base film, the slurry of the inorganic-organic hybrid coating comprises one or two of two materials: an inorganic substance, an organic polymer, a lithium supplement composite material and a phosphate flame retardant; the mass ratio of the inorganic substance, the organic polymer, the lithium supplement composite material and the phosphate flame retardant in the slurry of the inorganic-organic hybrid coating is 1: (0.05-0.20): (0.1-0.4): (0.01-0.08); and the mass proportion of lithium in the inorganic-organic hybrid coating is a, satisfying 0.1%≤a≤3%; the inorganic The mass proportion of the phosphate flame retardant in the organic-organic hybrid coating is b, satisfying 1%≤b≤5%; the positive electrode sheet includes a positive electrode current collector and a positive electrode coating coated on at least one surface of the positive electrode current collector, and the positive electrode active material in the positive electrode coating includes at least one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium iron phosphate and lithium manganese iron phosphate; the negative electrode sheet includes a negative electrode current collector and a negative electrode coating coated on at least one surface of the negative electrode current collector, and the negative electrode active material in the negative electrode coating includes at least two or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material and silicon-based alloy. The mass proportion of silicon in the negative electrode active material is 2%-30%; the mass fraction of silicon in the negative electrode sheet is c, the tensile strength of the diaphragm is T MPa, and the pore tortuosity of the diaphragm is τ, satisfying at least one of the following relationships: T≥120c+100; or 20c+1.6≥τ≥10c+1.6.

[0037] In some embodiments, specifically, the organic polymer includes a combination of at least one or more of aramid, polymethyl methacrylate and polyvinylidene fluoride; the inorganic substance includes a combination of at least one or more of boehmite, magnesium hydroxide, aluminum oxide, silicon oxide and zirconium oxide.

[0038] In some embodiments, the lithium supplement used in the lithium supplement composite material includes lithium carbonate (decomposition potential is about 4.8V), lithium oxalate (decomposition potential is about 4.3V), Li 2 NiO 2 (decomposition potential 3.5V, much lower than ordinary positive electrode materials), lithium quartz (decomposition potential 4.15V) and Li 2S (decomposition potential is lower than 3 V) and at least one or more combinations thereof. A composite material with small particle size and low decomposition potential is prepared by spray drying carbon nanotubes and lithium supplementing agent.

[0039] The lithium supplement agent is mixed with carbon nanotubes and then spray-dried to prepare a lithium supplement agent composite material, comprising the following steps:

[0040] Step S1, dispersing a lithium supplement agent and carbon nanotubes in NMP to prepare a liquid material;

[0041] Step S2, spraying the prepared liquid material evenly in the drying chamber through a nozzle, the nozzle usually being a rotating disc nozzle, a compressed air nozzle or a spray drying tower;

[0042] Step S3, the liquid material droplets after spray granulation are rapidly evaporated in the hot air flow to form solid particles; the temperature and humidity of the hot air flow of the spray drying are controlled within an appropriate range to ensure that the droplets are rapidly dried;

[0043] Step S4, the dried solid particles enter a cyclone separator or a centrifugal separator together with the hot air flow in the drying chamber; the solid particles are separated from the hot air flow by centrifugal force to obtain a lithium supplement composite material with a particle size of about 1 to 3 μm.

[0044] The mass content of carbon nanotubes in the lithium supplement composite material is 1% to 5%.

[0045] In some embodiments, specifically, the phosphate flame retardant includes at least one or more of triethyl phosphate (TEP), trimethyl phosphate (TMP), triisopropyl phosphate (TIPP), tri-n-butyl phosphate (TNBP), tri(2-chloropropyl) phosphate (TCPP), tri(2-chloroethyl) phosphate (TCEP), and triphenyl phosphate (TPHP).

[0046] In some embodiments, specifically, the base film includes any one of a polyethylene film, a polypropylene film, and a polyethylene / polypropylene composite film; the polyethylene / polypropylene composite film includes at least one layer of polyethylene film and at least one layer of polypropylene film; and the thickness of the base film is 7 μm-16 μm.

[0047] The lithium-ion cylindrical battery contains a winding core composed of a positive electrode sheet, a negative electrode sheet and a diaphragm designed with high energy density, as well as positive and negative busbars, an insulating sheet, an outer shell and a cap. The positive electrode tabs and negative electrode tabs are respectively arranged at the upper and lower parts of the cylindrical battery winding core. The cylindrical winding core is connected to the negative busbar by welding, and the negative busbar is connected to the outer shell by welding. The winding core is connected to the positive busbar by welding, an insulating sheet is placed on the positive busbar, and the positive busbar is connected to the cap by welding. The cap and the outer shell are sealed by rolling grooves. In the above cylindrical battery structure, the tabs can be a single tab, multiple tabs or a full tab, preferably a full tab, and the outer shell can be a steel shell or an aluminum shell. The diameter of the lithium-ion cylindrical battery is 20-50mm and the height is 50-150mm.

[0048] The scheme provided by the present invention is described in detail below in conjunction with the embodiments, but the embodiments do not limit the protection scope of the present invention, and other changes within the scope of the rights claimed by the present invention should also be included.

[0049] Test battery preparation method and steps:

[0050] 1. Homogenization:

[0051] The positive electrode material (such as lithium nickel cobalt aluminum oxide, conductive carbon black, binder PVDF, solvent NMP) and the negative electrode material (such as artificial graphite, conductive carbon black, single-walled carbon nanotubes, binder CMC, binder SBR, solvent deionized water) are weighed and mixed in a certain proportion to prepare positive and negative electrode slurries.

[0052] 2. Coating and rolling:

[0053] The positive electrode slurry is coated on aluminum foil with a thickness of 12±1 microns, and the negative electrode slurry is coated on copper foil with a thickness of 8±1 microns. The electrode pieces are baked in a blast oven to remove the solvent, and then the dried electrode pieces are rolled and cut.

[0054] 3. Winding:

[0055] The baked positive and negative electrode sheets are aligned parallel to the diaphragm, placed on a fully automatic winding machine, and wound to obtain a winding core.

[0056] 4. Battery cell assembly:

[0057] The positive busbar and negative busbar are welded to the winding core respectively, and then the negative busbar is welded to the steel shell. An insulating sheet is placed on top of the positive busbar, and the positive busbar is welded to the cap.

[0058] 5. Liquid filling and sealing:

[0059] The electrolyte is injected by vacuum injection, and the electrolyte is 1 mol / L LiPF 6The electrolyte (solvent is EC+DMC+DEC) is then sealed to obtain a cylindrical battery.

[0060] Example 1

[0061] This embodiment demonstrates a method for preparing a lithium-ion cylindrical battery according to the following steps.

[0062] Positive electrode preparation:

[0063] Nickel cobalt aluminum lithium (NCA88), conductive carbon black, and binder PVDF were weighed and mixed in a ratio of 96:2:2, and then NMP was added to adjust the solid content of the slurry to 60%, and then coated on aluminum foil, dried, rolled and cut to obtain the following Figure 3 The positive electrode is shown.

[0064] Negative electrode preparation:

[0065] Artificial graphite, silicon carbon, conductive carbon black, single-walled carbon nanotubes, binder CMC, and binder SBR were weighed and mixed in a ratio of 70:25:1:0.5:1.5:2, and then deionized water was added to adjust the slurry solid content to 40%, and then coated on copper foil, and then dried, rolled and cut to obtain Figure 4 The negative electrode is shown.

[0066] Preparation of organic-inorganic hybrid coating membrane:

[0067] (1) Preparation of coating slurry: 21 g polyvinylidene fluoride, 139 g alumina particles, 30 g Li 2 NiO 2 - CNT and 10 g of trimethyl phosphate (TMP) were dispersed in N-methylpyrrolidone (NMP), wherein the weight ratio of the solvent to the coated material was 10:1.

[0068] (2) Preparation of coated diaphragm: The slurry was coated onto a PE base film by gravure roller coating, and dried to obtain a diaphragm. Figure 2 The inorganic-organic hybrid coating shown has a thickness of 9 μm and a thickness of 3 μm.

[0069] The positive electrode sheet, negative electrode sheet and diaphragm are wound by a winding machine to form a winding core, in which the positive and negative electrode sheets are provided with non-coating areas, and this part is used as positive and negative pole ears. The winding core is cut and stacked for the positive and negative pole ears, and then the positive busbar and negative busbar are welded to the winding core respectively, and then the negative busbar is welded to the steel shell, and an insulating sheet is placed on top of the positive busbar, and the positive busbar is welded to the cap. Then the grooving, liquid injection, sealing and formation are completed to obtain a cylindrical battery.

[0070] The relevant parameters of this embodiment are as follows in Table 1:

[0071] Table 1 Lithium-ion cylindrical battery parameters of Example 1

[0072]

[0073]

[0074] Example 2: This example is the same as the method of Example 1, except that the base film type is a polypropylene film.

[0075] Example 3: This example is the same as the method of Example 1, except that the base film type is a polyethylene / polypropylene two-layer membrane.

[0076] Example 4: This example is the same as the method of Example 1, except that the base film thickness is 7 μm and the coating thickness is 2 μm.

[0077] Example 5: The method of this example is the same as that of Example 1, except that the thickness of the base film is 12 μm and the thickness of the coating is 4 μm.

[0078] Example 6: The method of this example is the same as that of Example 1, except that the thickness of the base film is 16 μm and the thickness of the coating is 5 μm.

[0079] Example 7: This example is the same as the method of Example 1, except that the type of the coating organic polymer is polymethyl methacrylate (PMMA).

[0080] Example 8: This example is the same as the method of Example 1, except that the type of the coating organic polymer is aramid.

[0081] Example 9: This example is the same as the method of Example 1, except that the inorganic type of the coating is silicon oxide.

[0082] Example 10: This example is the same as the method of Example 1, except that the coating inorganic material type is boehmite.

[0083] Example 11: This example is the same as the method of Example 1, except that the inorganic type of the coating is zirconium oxide.

[0084] Example 12: This example is the same as the method of Example 1, except that the coating inorganic substance type is magnesium hydroxide.

[0085] Example 13: This example is the same as Example 1, except that the amount of polyvinylidene fluoride (PVDF) added is 8 g, and the amount of aluminum oxide (Al 2 O 3 ) The coating addition amount is 152g.

[0086] Example 14: This example is the same as Example 1, except that the content of polyvinylidene fluoride (PVDF) is 15 g, and the content of aluminum oxide (Al 2 O 3 ) The coating addition amount is 145g.

[0087] Example 15: This example is the same as Example 1, except that the content of polyvinylidene fluoride (PVDF) is 27g, and the content of aluminum oxide (Al 2 O 3 )The coating addition amount is 133g.

[0088] Example 16: This example is the same as the method of Example 1, except that the CNT content in the lithium supplement composite material in the coating is 1%, and the lithium content in the coating is 1.97%.

[0089] Example 17: This example is the same as the method of Example 1, except that the CNT content in the lithium supplement composite material in the coating is 2%, and the lithium content in the coating is 1.95%.

[0090] Example 18: This example is the same as the method of Example 1, except that the CNT content in the lithium supplement composite material in the coating is 4%, and the lithium content in the coating is 1.91%.

[0091] Example 19: This example is the same as the method of Example 1, except that the CNT content in the lithium supplement composite material in the coating is 5%, and the lithium content in the coating is 1.89%.

[0092] Example 20: This example is the same as the method of Example 1, except that the type of lithium supplement in the lithium supplement composite material in the coating is lithium carbonate, and the lithium content in the coating is 2.73%.

[0093] Example 21: This example is the same as the method of Example 1, except that the type of lithium supplement in the lithium supplement composite material in the coating is lithium squarate, and the lithium content in the coating is 0.82%.

[0094] Example 22: This example is the same as the method of Example 1, except that the type of lithium supplement in the lithium supplement composite material in the coating is lithium oxalate, and the lithium content in the coating is 1.98%.

[0095] Example 23: This example is the same as the method of Example 1, except that the type of lithium supplement in the lithium supplement composite material in the coating is Li2S, and the lithium content in the coating is 2.64%.

[0096] Example 24: This example is the same as the method of Example 1, except that the amount of lithium supplement composite material added to the coating is 14 g, and the lithium content in the coating is 1.0%.

[0097] Example 25: This example is the same as the method of Example 1, except that the amount of lithium supplement composite material added to the coating is 22 g, and the lithium content in the coating is 1.5%.

[0098] Example 26: This example is the same as the method of Example 1, except that the amount of lithium supplement composite material added to the coating is 41 g, and the lithium content in the coating is 2.5%.

[0099] Example 27: This example is the same as the method of Example 1, except that the amount of lithium supplement composite material added to the coating is 52 g, and the lithium content in the coating is 3.0%.

[0100] Example 28: This example is the same as the method of Example 1, except that the flame retardant type in the coating is triethyl phosphate (TEP).

[0101] Example 29: This example is the same as the method of Example 1, except that the flame retardant type in the coating is triisopropyl phosphate (TIPP).

[0102] Example 30: This example is the same as the method of Example 1, except that the flame retardant type in the coating is tri-n-butyl phosphate (TNBP).

[0103] Example 31: This example is the same as the method of Example 1, except that the amount of flame retardant added to the coating is 8 g, while the amount of flame retardant added is 4%.

[0104] Example 32: This example is the same as the method of Example 1, except that the amount of flame retardant added to the coating is 6g, while the amount of flame retardant added is 3%.

[0105] Example 33: This example is the same as the method of Example 1, except that the amount of flame retardant added to the coating is 4g, while the amount of flame retardant added is 2%.

[0106] Example 34: This example is the same as the method of Example 1, except that the amount of flame retardant added to the coating is 2g, while the amount of flame retardant added is 1%.

[0107] Example 35: This example is the same as the method of Example 1, except that the silicon content in the negative electrode active material is 5%.

[0108] Example 36: This example is the same as the method of Example 1, except that the silicon content in the negative electrode active material is 20%.

[0109] Example 37: This example is the same as the method of Example 1, except that the silicon content in the negative electrode active material is 30%.

[0110] Comparative Example 1: This comparative example is the same as the method of Example 1, except that the base film is coated with a coating.

[0111] Comparative Example 2: This comparative example is the same as Example 1, except that an organic polymer is added to the coating.

[0112] Comparative Example 3: This comparative example is the same as Example 1, except that inorganic ceramic particles are added to the coating.

[0113] Comparative Example 4: This comparative example is the same as Example 1, except that the coating is added with a lithium supplement composite material.

[0114] Comparative Example 5: This comparative example is the same as Example 1, except that the CNT mass content in the lithium supplement composite material is 0%, and the lithium content in the coating is 1.99%.

[0115] Comparative Example 6: This comparative example is the same as Example 1, except that a flame retardant is added to the coating.

[0116] Comparative Example 7: This comparative example is the same as Example 1, except that the amount of the coating lithium supplement composite material added is 100 g, and the lithium content in the coating is 4.77%.

[0117] Comparative Example 8: This comparative example is the same as Example 1, except that the amount of flame retardant added to the coating is 50 g.

[0118] Comparative Example 9: This comparative example is the same as the method of Example 1, except that the base film thickness is 5 μm and the coating thickness is 1 μm.

[0119] Comparative Example 10: This comparative example is the same as the method of Example 1, except that the base film thickness is 25 μm and the coating thickness is 8 μm.

[0120] Comparative Example 11: This comparative example is the same as Example 1, except that the silicon content in the negative electrode active material is 40%.

[0121] For Examples 1 to 37 and Comparative Examples 1 to 11, the performance of the separator and the battery was evaluated, and the test items included:

[0122] Diaphragm mechanical properties test: tensile strength, refer to GB / T1040.3-2006.

[0123] Diaphragm thermal stability test: 1h thermal shrinkage test at 120℃, refer to GB / T36363-2018.

[0124] Diaphragm flame retardant performance test: Limiting oxygen index test, refer to GB2406-80 (plastics).

[0125] Diaphragm electrolyte wettability test: liquid absorption rate, refer to QB / T 2303.11-2008 "Battery pulp paper Part 11: Determination of liquid absorption rate".

[0126] Diaphragm pore tortuosity test: τ = (Rion·S·ε·σ) / d, τ is tortuosity; Rion is ionic resistance; S is diaphragm area; ε is diaphragm porosity; σ is electrolyte conductivity; d is diaphragm thickness. (Rion test reference GB / T36363-2018)

[0127] Diaphragm ion conductivity test, refer to GB / T36363-2018.

[0128] Battery electrochemical performance test: battery cycle performance test.

[0129] The battery cycle performance test takes the NCA88+graphite / silicon carbon cylindrical battery test as an example. For other types of batteries, the test step parameters need to be modified.

[0130] Place the cylindrical battery in a constant temperature oven at 25°C for more than 6 hours and test it according to the following steps:

[0131] (1) The cylindrical battery was discharged at a constant current of 0.1C to a cutoff of 2.5V and allowed to stand for 10 minutes;

[0132] (2) The cylindrical battery was charged at a constant current of 0.1C to a cutoff of 4.2V, and then at a constant voltage of 0.01C to a cutoff, and then allowed to stand for 10 minutes;

[0133] (3) The cylindrical battery was discharged at a constant current of 0.1C to a cutoff of 2.5V, and then left to stand for 10 minutes, and the capacity value at this time was read;

[0134] (4) Charge the battery at a constant current of 1.0C to 4.2V, and charge at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;

[0135] (5) Discharge the battery at a constant current of 1.0C to a cutoff of 2.5V and let it stand for 10 minutes;

[0136] (6) Repeat steps (4) and (5) 600 times;

[0137] (7) The cycle performance of a single battery, i.e., the capacity retention rate, is obtained by calculating the ratio of the 600th discharge capacity to the first discharge capacity in steps (4) and (5).

[0138] Battery thermal safety performance test: adiabatic temperature rise characteristics test, refer to GB / T36276-2023.

[0139] Battery electrical safety performance test: overcharge / overdischarge performance test, short circuit performance test, refer to GB / T36276-2023.

[0140] 200 cycles of lithium content test in the diaphragm coating:

[0141] Take at least 6 cylindrical batteries, place them in a 25℃ constant temperature box for more than 6 hours, and test them according to the following steps:

[0142] (1) The cylindrical battery was discharged at a constant current of 0.1C to a cutoff of 2.5V and allowed to stand for 10 minutes;

[0143] (2) The cylindrical battery was charged at a constant current of 0.1C to a cutoff of 4.2V, and then at a constant voltage of 0.01C to a cutoff, and then allowed to stand for 10 minutes;

[0144] (3) The cylindrical battery was discharged at a constant current of 0.1C to a cutoff of 2.5V, and then left to stand for 10 minutes, and the capacity value at this time was read;

[0145] (4) Select cylindrical batteries with a capacity value difference of less than 3%;

[0146] (5) Take three of the batteries, disassemble them to obtain the separators, soak the separators in DMC for 4 h, clean them, and then put them in a 60°C vacuum oven for 6 h;

[0147] (6) Scrape the mixed coating on the diaphragm, digest its powder and test ICP, take the average value, and obtain the Li element content a in the mixed coating of the diaphragm;

[0148] (7) Test at least three other batteries for 200 cycles using the following procedure:

[0149] (7.1) Charge the battery at a constant current of 1.0C to 4.2V, and charge at a constant voltage of 0.05C to cut off, and let stand for 5 minutes;

[0150] (7.2) Discharge the battery at a constant current of 1.0C to 2.5V cutoff, and let it stand for 5 minutes;

[0151] (7.3) Repeat steps (7.1) and (7.2) 200 times, disassemble at least three batteries to obtain the separator, scrape the mixed coating, digest the powder, digest the powder and test the ICP, take the average value, and obtain the Li element content b in the separator mixed coating;

[0152] The test results are as follows:

[0153] 1. Whether the base film is coated or not, the performance comparison is shown in Table 2.

[0154] Table 2 Comparison of base film coating performance

[0155]

[0156] According to the results in Table 2, through the performance comparison between Example 1 and Comparative Example 1, coating the surface of the base film helps to improve the mechanical properties of the diaphragm, improve thermal stability and flame retardancy, and improve the cycle performance of the battery.

[0157] 2. Base film type, performance comparison is shown in Table 3.

[0158] Table 3 Performance comparison of base film types

[0159]

[0160] According to the results in Table 3, through the performance comparison between Example 1, Example 2 and Example 3, the PP film has better mechanical properties and thermal stability, and the PE film has better electrolyte wettability. The PE / PP composite separator can combine the advantages of the two base films.

[0161] 3. Base film and coating thickness, performance comparison is shown in Table 4.

[0162] Table 4 Comparison of base film and coating thickness performance

[0163]

[0164] According to the results in Table 4, by comparing Example 1 with Examples 4-6, it can be seen that the thickness of the diaphragm and coating increases, the tensile strength of the diaphragm increases, the pore tortuosity increases, the stress generated by the volume expansion of silicon during the battery charging and discharging process is relieved, and the safety performance of the battery is enhanced. The thickness of the diaphragm coating increases, the overall pore structure of the diaphragm is changed, the ion transmission path becomes longer, the diaphragm pore tortuosity increases, the ion conductivity decreases, the diaphragm impedance is large, and the battery cycle performance decreases. In addition, due to the increase in diaphragm thickness, the volume energy density of the cylindrical battery decreases. By comparing Example 1 with Comparative Examples 8-9, when the diaphragm thickness is too low (5+1μm), although the battery volume energy density increases, the tensile strength of the diaphragm decreases significantly, the volume expansion effect of silicon is easy to cause damage to the diaphragm, and the battery cycle performance and safety performance decrease. When the diaphragm thickness is too high (25+8), the ion conductivity of the diaphragm decreases, the pore tortuosity is extremely high, the impedance is large, the cycle performance decreases sharply, and the battery energy density is low.

[0165] 4. Types of coating organic polymers and inorganic substances, performance comparison is shown in Table 5.

[0166] Table 5 Performance comparison of coating organic polymer and inorganic type

[0167]

[0168] In some embodiments, specifically, Table 5

[0169] According to the results in Table 5, by comparing Example 1 with Examples 7-12, it can be seen that the inorganic-organic hybrid coating of the diaphragm can enhance the mechanical properties, improve the ionic conductivity, improve the thermal stability, and enhance the cycle performance. However, the electrolyte wettability, thermal stability, and mechanical strength improvement of different organic polymer and inorganic coating diaphragms are different. For example, PMMA has poorer thermal stability than PVDF and aramid, and has a higher thermal shrinkage rate; ZrO 2 The ionic conductivity is strong, and the ionic conductivity of the coated diaphragm is high. The pass rate of the battery temperature rise test is related to the thermal stability of the diaphragm. The mixed coating improves the thermal stability of the diaphragm and the pass rate of the battery temperature rise test is high.

[0170] 5. The performance comparison of the coating organic polymer and inorganic content is shown in Table 6.

[0171] Table 6 Performance comparison of coating organic polymer and inorganic content

[0172]

[0173] According to the results in Table 6, by comparing Example 1 with Examples 13-15, it can be seen that the organic polymer in the diaphragm coating is beneficial to improving the tensile strength of the diaphragm, the electrolyte wettability of the diaphragm is improved, the liquid absorption rate and ionic conductivity are improved, which is beneficial to inhibiting the growth of lithium dendrites and improving the cycle performance. When the organic polymer content is too high, dissolving in NMP may cause the base membrane to block the pores, resulting in a decrease in ionic conductivity and affecting the battery cycle performance. When the organic polymer content in the coating is too little, the tensile strength of the diaphragm is greatly reduced. During the expansion process of negative electrode lithium insertion, the diaphragm is subject to the expansion stress and there is a risk of fracture failure. The inorganic matter in the diaphragm coating is mainly beneficial to improving the thermal stability of the diaphragm, reducing the thermal shrinkage of the diaphragm, and having a high pass rate for the temperature rise test and the short circuit test. By comparing Example 1 with Comparative Example 2 and Comparative Example 3, the mechanical properties, electrolyte wettability, thermodynamic properties and cycle performance of the organic single inorganic or organic coating diaphragm are quite different from those of the mixed coating diaphragm, and the pass rates of the temperature rise test and the short circuit test are low, and the comprehensive performance is difficult to meet the requirements of high energy density cylindrical batteries.

[0174] 6. The performance comparison of different CNT addition amounts in lithium supplement composite materials is shown in Table 7

[0175]

[0176] According to the results in Table 7, by comparing Example 1 with Examples 16-19, it can be seen that the increase in the CNT content in the lithium supplement composite material improves the conductivity, reduces the decomposition potential of the lithium supplement, increases the decomposition efficiency, and improves the battery cycle performance. When the CNT content increases to 3%, the cycle performance is limited, indicating that the CNT improves the decomposition efficiency of the lithium supplement to the limit. When the CNT content is 0%, the amount of lithium supplement decomposed is very small, it is difficult to achieve a continuous lithium supplement effect, and the cycle performance is poor.

[0177] 7. The performance comparison of different lithium supplement types is shown in Table 8.

[0178] Table 8 Performance comparison of different lithium supplement types

[0179]

[0180] According to the results in Table 8, by comparing Example 1 with Examples 20-23, it can be seen that different types of lithium supplement agents added to the diaphragm coating have different effects on improving the battery cycle performance. The lithium supplement agent that is easily decomposed during the cycle can replenish the loss of active lithium, and the battery capacity retention rate is relatively high. Lithium carbonate (decomposition potential is about 4.8V), lithium oxalate (decomposition potential is about 4.3V), Li 2 NiO 2 (decomposition potential 3.5V, much lower than ordinary positive electrode materials), lithium quartz (decomposition potential 4.15V) and Li 2 S (decomposition potential is lower than 3V), carbon nanotubes are compounded with lithium supplement agents by spray drying to reduce the decomposition potential of the lithium supplement agent. The higher the decomposition efficiency of the lithium supplement agent, the better the effect of improving the battery cycle stability. In addition, the decomposition and gas production of lithium carbonate when the battery is overcharged helps the current cut-off device (CID) to open, cut off the circuit, and improve safety performance. By comparing Example 1 and Comparative Example 4, it can be seen that if the lithium supplement agent composite material is not added to the diaphragm coating, the loss of active lithium in the battery cannot be supplemented, and the battery cycle performance is poor.

[0181] 8. Lithium content of coating. Performance comparison is shown in Table 9.

[0182] Table 9 Comparison of coating lithium content performance

[0183]

[0184]

[0185] According to the results in Table 9, by comparing Example 1 and Examples 24-27, it can be seen that when the amount of lithium supplement composite material added in the diaphragm coating increases, the battery cycle performance is improved, but the tensile strength of the diaphragm will decrease slightly, and the thermal shrinkage rate will increase, affecting the mechanical properties and thermodynamic stability of the diaphragm. In addition, when the amount added increases, the pores of the diaphragm may be blocked, causing the liquid absorption rate of the diaphragm to decrease. By comparing Example 1 and Comparative Example 7, when the amount of lithium supplement added is too much, more side reactions may occur with the electrolyte during the charge and discharge process, and decompose at high potential, thereby deteriorating the cycle performance of the battery. In addition, the mechanical strength of the diaphragm is low and the thermal shrinkage rate is high, which cannot meet the safety performance requirements of cylindrical batteries.

[0186] 9. Flame retardant types and performance comparison are shown in Table 10.

[0187] Table 10 Flame retardant type performance comparison

[0188]

[0189]

[0190] According to the results in Table 10, by comparing Example 1 and Examples 28-30, it can be seen that the flame retardant effect of different phosphate flame retardants is related to the length of the alkyl chain in its molecular structure. The shorter the alkyl chain length, the better the thermal stability and the better the flame retardant effect. The performance of the four flame retardants is different, but their limiting oxygen index is higher than 35%. By comparing Example 1 with Comparative Example 6, when no flame retardant is added, the limiting oxygen index of the diaphragm is low, and it is very easy to burn in the air at high temperature. Flame retardants can be combined with organic polymers in the form of hydrogen bonds or van der Waals forces. Flame retardants cannot get rid of the constraints of organic polymers and are released in the electrolyte, which reduces the effect of flame retardants directly added to the electrolyte on viscosity and ionic conductivity, and helps to improve the battery cycle performance. In addition, phosphate flame retardants can act as hydrogen bond receptors to limit the activity of free water and reduce the generation of HF during charging and discharging, thereby protecting the SEI film from corrosion and improving the cycle stability of the battery.

[0191] 10. Flame retardant content. Performance comparison is shown in Table 11.

[0192] Table 11 Flame retardant content performance comparison

[0193]

[0194] According to the results in Table 11, by comparing Example 1 and Examples 31-34, it can be seen that when the amount of flame retardant added in the diaphragm coating increases, the battery cycle performance is improved, but the tensile strength and liquid absorption rate of the diaphragm will decrease accordingly. Since the amount of flame retardant added is small, the effect on the battery cycle performance is small. By comparing Example 1 and Comparative Example 8, when the amount of flame retardant added is too much, the tensile strength and liquid absorption rate of the diaphragm are greatly reduced, and the ionic conductivity of the diaphragm is reduced, thereby deteriorating the battery cycle performance.

[0195] 11. Silicon content in negative electrode active materials, performance comparison is shown in Table 12

[0196] Table 12 Comparison of silicon content performance of negative electrode active materials

[0197]

[0198] According to the results in Table 12, by comparing Example 1 with Examples 35-37, it can be seen that as the silicon content in the negative electrode active material increases, the volume expansion of silicon causes the negative electrode to continuously produce new interfaces, resulting in increased loss of active lithium and reduced cycle performance. In addition, the greater stress generated by the volume expansion of silicon may cause fatigue damage to the diaphragm, thereby causing a short circuit in the battery. By comparing Example 1 with Comparative Example 11, when the silicon content in the negative electrode active material is too high, due to the increase in silicon content, the conductivity of the negative electrode is poor and the impedance is large, which may cause excessive heat generation during charging and discharging, and a low pass rate for overcharge and overdischarge tests.

[0199] In summary, the present lithium-ion cylindrical battery and its preparation method can decompose during the battery charge and discharge cycle by adding a lithium replenisher composite material to the inorganic-organic hybrid coating of the diaphragm, thereby achieving continuous lithium replenishment. The flame retardant cannot be released into the electrolyte due to the restraint of the organic polymer, which reduces the effect of the flame retardant directly added to the electrolyte on the viscosity and ionic conductivity, and helps to improve the battery cycle performance. In addition, phosphate flame retardants can act as hydrogen bond acceptors to limit the activity of free water and reduce the generation of HF during the charge and discharge process, thereby protecting the SEI film from corrosion and improving the interface stability of the negative electrode. At the same time, the organic-inorganic hybrid coating can improve the electrolyte wettability of the diaphragm, increase the liquid absorption rate and ion conductivity of the diaphragm, inhibit the growth of lithium dendrites, and improve the battery cycle stability; the inorganic ceramic particles added to the diaphragm coating can improve the thermal stability of the diaphragm, and the organic high molecular polymer added to the diaphragm coating has good adhesion. When mixed with inorganic materials, it can enhance the mechanical properties of the diaphragm, effectively alleviate the silicon volume expansion stress, and reduce the risk of fatigue damage to the diaphragm; the decomposition products of the flame retardant added to the diaphragm coating at high temperature can isolate oxygen and heat, inhibit the combustion process, and reduce the risk of thermal runaway.

[0200] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A lithium-ion cylindrical battery, comprising a shell, a winding core located in the shell, and an electrolyte, characterized in that: The winding core is formed by winding a positive electrode sheet, a separator and a negative electrode sheet together. The separator includes a base film and an inorganic-organic hybrid coating coated on the base film. The slurry of the inorganic-organic hybrid coating includes an inorganic substance, an organic polymer, and at least one of a lithium supplement composite material and a phosphate flame retardant.

2. The lithium-ion cylindrical battery according to claim 1, characterized in that: The mass ratio of the inorganic substance, the organic polymer, the lithium supplement composite material and the phosphate flame retardant in the slurry of the inorganic-organic hybrid coating is 1: (0.05-0.20): (0.1-0.4): (0.01-0.08); and The mass content of lithium element in the inorganic-organic hybrid coating is a, which satisfies 0.1%≤a≤3%; The mass content of the phosphate flame retardant in the inorganic-organic mixed coating is b, satisfying 1%≤b≤5%.

3. The lithium-ion cylindrical battery according to claim 1, characterized in that: The organic polymer comprises at least one or more of aramid, polymethyl methacrylate and polyvinylidene fluoride; The inorganic substance includes at least one or more of boehmite, magnesium hydroxide, aluminum oxide, silicon oxide and zirconium oxide.

4. The lithium-ion cylindrical battery according to claim 1, characterized in that: The lithium supplement used in the lithium supplement composite material includes at least one or more of lithium carbonate, lithium oxalate, Li2NiO2, lithium squarate and Li2S.

5. The lithium-ion cylindrical battery according to claim 4, characterized in that: The lithium supplement agent is mixed with carbon nanotubes and then spray-dried to prepare a lithium supplement agent composite material, comprising the following steps: Step S1, dispersing a lithium supplement agent and carbon nanotubes in NMP to prepare a liquid material; Step S2, spraying the prepared liquid material evenly in the drying chamber through a nozzle, the nozzle adopts a rotating disc nozzle, a compressed air nozzle or a spray drying tower; Step S3, after spray granulation of liquid material droplets in the hot air flow quickly evaporate to form solid particles; Step S4, the dried solid particles enter a cyclone separator or a centrifugal separator together with the hot air flow in the drying chamber; the solid particles are separated from the hot air flow by centrifugal force to obtain a lithium supplement composite material with a particle size of 1 to 3 μm; Among them, the mass content of carbon nanotubes in the lithium supplement composite material is 1%~5%.

6. The lithium-ion cylindrical battery according to claim 1, characterized in that: The phosphate flame retardant includes at least one or more combinations of triethyl phosphate, trimethyl phosphate, triisopropyl phosphate, tri-n-butyl phosphate, tri(2-chloropropyl) phosphate, tri(2-chloroethyl) phosphate, and triphenyl phosphate.

7. The lithium-ion cylindrical battery according to claim 2, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode coating coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material in the positive electrode coating comprises a combination of at least one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium iron phosphate and lithium manganese iron phosphate; The negative electrode sheet comprises a negative electrode current collector and a negative electrode coating coated on at least one surface of the negative electrode current collector, the negative electrode active material in the negative electrode coating comprises at least two or a combination of more than two of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material and silicon-based alloy, and the silicon mass fraction c in the negative electrode sheet coating is 2%-30%.

8. The lithium-ion cylindrical battery according to claim 7, wherein the mass content a of lithium in the separator coating and the mass content c of silicon in the negative electrode coating satisfy: 0.4≥a / c≥0.

05.

9. The lithium-ion cylindrical battery according to claim 7, characterized in that: The silicon mass fraction in the negative electrode coating is c, the tensile strength of the separator is T MPa, the pore tortuosity of the separator is τ, and at least one of the following relationships is satisfied: T≥120c+100; 20c+1.6≥τ≥10c+1.

6.

10. The lithium-ion cylindrical battery according to claim 1, characterized in that: The base film comprises any one of a polyethylene film, a polypropylene film, and a polyethylene / polypropylene composite film; The polyethylene / polypropylene composite film comprises at least one layer of polyethylene film and at least one layer of polypropylene film; and The base film has a thickness of 7 μm-16 μm.

11. The lithium ion cylindrical battery according to any one of claims 1 to 9, characterized in that: The lithium-ion cylindrical battery has a diameter of 18-50 mm and a height of 50-150 mm.

12. A method for preparing a lithium ion cylindrical battery according to any one of claims 1 to 10, characterized in that: The steps include: Step S1, dispersing an inorganic substance, an organic polymer, and one or both of a lithium supplement composite material and a phosphate flame retardant in an organic solvent to form a mixed dispersion, and adjusting the solid content to obtain a coating slurry; Step S2, coating the slurry on at least one side of the base film, and drying to form an inorganic-organic hybrid coating with a thickness of 2-5 μm to obtain a composite diaphragm; Step S3, wind the positive electrode sheet, the separator and the negative electrode sheet together to form a winding core, the edges of the positive and negative electrodes are provided with empty foil areas, one end of the cylindrical winding core is connected to the negative electrode bus bar by welding, the negative electrode bus bar is connected to the outer shell by welding, the other end of the cylindrical winding core is connected to the positive electrode bus bar by welding, an insulating sheet is placed on the positive electrode bus bar, the positive electrode bus bar is connected to the cap by welding, and then the electrolyte is injected, and finally the groove is rolled and sealed to obtain a lithium-ion cylindrical battery.

Citation Information

Cited By

  • Composite diaphragm, preparation method and lithium ion battery

    CN121123569A